Preparation method and application of nanocomb polymer extreme pressure lubricant for drilling fluid
The nanocomb polymer extreme pressure lubricant was prepared by emulsion polymerization, which solved the problems of poor lubricity and poor efficiency under high temperature, high pressure, high salt and high density conditions, and achieved good lubricity and efficiency.
Patent Information
- Application Number
- CN202311010878.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-10
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-08-10
AI Technical Summary
The existing lubricants for drilling fluids have poor lubricity and poor efficiency under high temperature, high pressure, high salt and high density conditions, and have insufficient temperature and salt resistance.
The nanocomb polymer extreme pressure lubricant was prepared by emulsion polymerization method, and water-insoluble monomers such as acrylate monomers, hydrophobic cationic monomers and styrene were stably dispersed in water, and a free radical polymerization reaction was initiated by a water-soluble initiator to form a comb structural polymer, and mixed with an extremely pressure antiwear agent, a solid sacrificial agent and a white oil.
It achieves good lubricating performance and efficiency under high temperature, high pressure, high salt and high density conditions, extends the service life of the drill bit and reduces drill tool wear.
Smart Images

Figure BDA0004390093990000091 
Figure BDA0004390093990000101 
Figure HDA0004390094010000011
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of petroleum drilling, and in particular relates to a preparation method and application of a nano-comb polymer extreme pressure lubricant for drilling fluid. Background Art
[0002] With the continuous reduction of conventional oil and gas resources, deep, ultra-deep and unconventional oil and gas resources have become an important direction for the development of oil and gas resources. The formation pressure of deep and ultra-deep wells is high. The use of high-density water-based drilling fluids leads to an increase in the pressure difference between the drilling fluid and the formation pressure, and the thick filter cake, which is easy to cause pressure differential drilling accidents. At the same time, under the action of high temperature and high pressure, the drill bit is cut under high load conditions, and the drill tool is also very easy to wear when it rotates under high speed conditions. Unconventional resources are generally developed using long horizontal wells. With the continuous extension of the horizontal section, the horizontal section drag pressure is serious, resulting in a decrease in drilling speed, an increase in the difficulty of directional drilling, and a large friction resistance of the casing. Adding high-efficiency lubricants to the drilling fluid can effectively reduce the friction between the drill pipe and the well wall, reduce the drilling torque of deep and ultra-deep wells and the friction resistance of horizontal wells, thereby preventing pressure differential drilling and improving drilling pressure transmission. The research results show that the use of extreme pressure lubricants can also form extreme pressure lubricating films on the metal surface, reduce drilling tool wear, and extend the service life of the drill bit.
[0003] However, deep and ultra-deep well drilling often faces the problem of high temperature, high pressure and high salt. The currently commonly used lubricants such as alcohol ethers, esters, and amides have low temperature resistance, and their lubrication performance will be greatly reduced in salt mudstone inhibitors such as potassium chloride, organic salts and sodium chloride. The currently commonly used high temperature and salt resistant drilling fluid lubricants mainly include solid lubricants and liquid lubricants. Solid lubricants include graphite, plastic balls, etc., but solid lubricants are easily removed by vibrating screens, and after being sheared and crushed by pressure during drilling, the lubrication performance is significantly reduced and the loss is high. Liquid lubricants mainly include diesel-based lubricants, mineral oil-based lubricants, asphalt lubricants, etc., but these lubricants have poor dispersibility in water-based drilling fluids and have a certain impact on the environment.
[0004] At present, the commonly used high temperature and salt resistant lubricants have the problems of low extreme pressure film strength, poor lubrication retention, insufficient temperature and salt resistance, and significantly reduced lubricity in high-density drilling fluids in actual field applications. Therefore, it is of great significance to develop a lubricant with good lubrication performance under high temperature, high pressure, high salt and high density conditions. Summary of the invention
[0005] The purpose of the present invention is to provide a preparation method and application of a nanocomb polymer extreme pressure lubricant for drilling fluid, so as to overcome the problems of poor lubrication persistence, insufficient temperature and salt resistance, and significantly reduced lubricity in high-density drilling fluid existing in existing lubricants for drilling fluid.
[0006] In order to solve the above problems, the present invention adopts the following technical solutions:
[0007] A method for preparing a nanocomb polymer extreme pressure lubricant for drilling fluid comprises the following steps:
[0008] S1, dissolving allyl polyoxyethylene ether and a strong adsorption monomer in deionized water to prepare a mixed solution, adjusting the pH of the mixed solution to 7.0-8.0, adding emulsifier A and stirring evenly;
[0009] S2, continue to add acrylate monomer, hydrophobic cationic monomer, styrene and emulsifier B in sequence and perform pre-emulsification;
[0010] S3, adding an initiator after heating in a nitrogen environment, and cooling after the reaction is completed to obtain a nano-lubricating rubber brush;
[0011] S4, mixing the nano-lubricating rubber brush, the extreme pressure anti-wear agent, the solid sacrificial agent and the white oil to obtain the nano-comb type polymer extreme pressure lubricant.
[0012] Furthermore, the concentration of the mixed solution is 15% to 25%, and the mass ratio of allyl polyoxyethylene ether to the strong adsorption monomer is (3 to 5): (2 to 4).
[0013] Furthermore, the mass ratio of the emulsifier A, acrylate monomer, hydrophobic cationic monomer, styrene, emulsifier B, initiator and the total mass of allyl polyoxyethylene ether and strongly adsorbing monomer is (1-2):(3-5):(2-4):(4-6):(1-3):(0.1-0.2):10.
[0014] Furthermore, the allyl polyoxyethylene ether is selected from one or more of APEG 350, APEG 400 and APEG 500.
[0015] Furthermore, the strong adsorption monomer is selected from one or more of acrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, and 2-acrylamide-2-methylpropanesulfonic acid.
[0016] Furthermore, the emulsifier A adopts a Tween series emulsifier, and the Tween series emulsifier is selected from one or more of Tween 40, Tween 60 and Tween 80; the emulsifier B adopts a Span series emulsifier, and the Span series emulsifier is selected from one or more of Span 20, Span 40 and Span 60.
[0017] Furthermore, the acrylate monomer is selected from one or more of octadecyl acrylate, polyethylene glycol monomethyl ether acrylate, 2-dodecyl acrylate, and lauryl methacrylate.
[0018] Furthermore, the hydrophobic cationic monomer is selected from one or more of dodecyldimethylallylammonium chloride, tetradecyldimethylallylammonium chloride, hexadecyldimethylallylammonium chloride, and carboxymethyloctadecylmethyldiallylammonium chloride.
[0019] Furthermore, the volume ratio of the nano-lubricating rubber brush, the extreme pressure anti-wear agent, the solid sacrificial agent and the white oil is (7-10): (1-3): (3-5): (80-100).
[0020] A water-based drilling fluid comprises a nano-comb polymer extreme pressure lubricant prepared by the method.
[0021] Compared with the prior art, the present invention has the following beneficial technical effects:
[0022] The invention provides a method for preparing a nano-comb polymer extreme pressure lubricant for drilling fluid. The method adopts an emulsion polymerization method, wherein water-insoluble monomers such as acrylate monomers, hydrophobic cationic monomers and styrene are stably dispersed in water, and a water-soluble initiator is used to initiate a free radical polymerization reaction to generate a comb-structured polymer, wherein the comb-structured polymer has good temperature and salt resistance. Finally, the comb-structured polymer, an extreme pressure anti-wear agent, a solid sacrificial agent and white oil are mixed to obtain the nano-comb polymer extreme pressure lubricant. The hydrophobic side chains are extended in a high-salinity liquid phase to form a lubricating layer together with the white oil for lubrication. The solid sacrificial agent has good temperature resistance and lubricity and is interspersed in the comb-type side chains of the comb-type polymer. When friction between contact surfaces is stressed, the solid particles have a shear-slip effect similar to that of graphite and play a "force unloading" role. On the one hand, the lubrication effect is achieved, and on the other hand, the comb-structured side chains are protected to maintain the lubrication effect, thereby ensuring that the lubricant has good lasting effect. The extreme pressure anti-wear agent can form an extreme pressure chemical protective film on the surface of a metal drilling tool, has a certain filtration loss reduction effect, and ensures that the lubricant has good extreme pressure lubrication performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 The flowchart of the preparation method of the nanocomb type polymer extreme pressure lubricant for drilling fluid in the embodiment of the present invention. DETAILED DESCRIPTION
[0024] In order to enable those skilled in the art to better understand the scheme of the present invention, the technical scheme in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0025] It should be noted that the terms "first", "second", etc. in the specification and claims of the present invention and the above-mentioned drawings are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the data used in this way can be interchanged where appropriate, so that the embodiments of the present invention described herein can be implemented in an order other than those illustrated or described herein. In addition, the terms "including" and "having" and any variations thereof are intended to cover non-exclusive inclusions, for example, a process, method, system, product or device that includes a series of steps or units is not necessarily limited to those steps or units that are clearly listed, but may include other steps or units that are not clearly listed or inherent to these processes, methods, products or devices.
[0026] The present invention provides a method for preparing a nanocomb polymer extreme pressure lubricant for drilling fluid, such as Figure 1 As shown, the specific steps include:
[0027] S1, dissolving allyl polyoxyethylene ether and a strong adsorption monomer in deionized water to prepare a mixed solution, and adjusting the pH of the mixed solution to 7.0-8.0;
[0028] The mass ratio of allyl polyoxyethylene ether to the strong adsorption monomer is (3-5): (2-4), the concentration of the mixed solution is 15%-25%, the allyl polyoxyethylene ether can be selected from one or more of APEG 350, APEG 400 and APEG 500, and the strong adsorption monomer is acrylamide and its derivatives, including one or more of acrylamide, N, N-dimethylacrylamide, N, N-diethylacrylamide, and 2-acrylamide-2-methylpropane sulfonic acid.
[0029] The pH of the mixed solution is adjusted by using a sodium hydroxide solution with a mass fraction of 5% to 10%.
[0030] S2, adding a Tween series emulsifier to the mixed solution and stirring evenly, and then sequentially adding an acrylate monomer, a hydrophobic cationic monomer, styrene and a Span series emulsifier and performing pre-emulsification;
[0031] Specifically, the Tween series emulsifier is selected from one or more of Tween 40, Tween 60 and Tween 80, and the mass is 10% to 20% of the total mass of allyl polyoxyethylene ether and the strong adsorption monomer; the acrylate monomer is selected from one or more of octadecyl acrylate, polyethylene glycol monomethyl ether acrylate, 2-dodecyl acrylate, and lauryl methacrylate, and the mass is 30% to 50% of the total mass of allyl polyoxyethylene ether and the strong adsorption monomer; the hydrophobic cationic monomer is one or more of dodecyl dimethyl allyl ammonium chloride, tetradecyl dimethyl allyl ammonium chloride, hexadecyl dimethyl allyl ammonium chloride, and carboxymethyl octadecyl methyl diallyl ammonium chloride, and the mass is 20% to 40% of the total mass of allyl polyoxyethylene ether and the strong adsorption monomer; the mass of styrene is 40% to 60% of the total mass of allyl polyoxyethylene ether and the strong adsorption monomer; the Span series emulsifier includes Span 20, Span 40 and Span One or more of 60, the mass of which is 10% to 30% of the total mass of the allyl polyoxyethylene ether and the strongly adsorbent monomer.
[0032] After adding the Tween series emulsifier, use a magnetic stirrer to stir it to fully dissolve it, and pre-emulsification is completed using a shear emulsifier.
[0033] S3, after the pre-emulsification is completed, the mixture is transferred to a reaction device, the initiator is added after the temperature is raised in a nitrogen environment, and the nano-lubricating rubber brush is obtained after cooling;
[0034] Specifically, the temperature is raised to 75-85° C. in a nitrogen environment, and an initiator is added and stirred for 4-6 hours. The initiator is ammonium persulfate, and the mass is 1%-2% of the total mass of allyl polyoxyethylene ether and the strong adsorption monomer. After cooling, the nano-lubricating rubber brush can be obtained.
[0035] S4, mixing the nano-lubricating rubber brush, the extreme pressure anti-wear agent, the solid sacrificial agent and the white oil to obtain a nano-comb polymer extreme pressure lubricant
[0036] In order to enhance the performance of the lubricant, the nano-lubricating rubber brush obtained by the reaction can be uniformly mixed with the extreme pressure anti-wear agent, the solid sacrificial agent and the white oil in a ratio of (7-10): (1-3): (3-5): (80-100);
[0037] The extreme pressure anti-wear agent can be one or more of zinc dialkyl dithiophosphate, aminothioester T323 and organic molybdenum (dialkyl dithiophosphate oxymolybdenum, dialkyl dithiophosphate sulfide oxymolybdenum, dialkyl disulfide carbamate sulfide oxymolybdenum, dialkyl dithiocarbamate molybdenum), the solid sacrificial agent can be one or more of 2000 mesh boron nitride, 200 mesh elastic graphite, 800 mesh talc, and the white oil can be one or more of 3# white oil, 5# white oil, 7# white oil, and 10# white oil.
[0038] The present invention also protects a water-based drilling fluid, comprising the nano-comb polymer extreme pressure lubricant prepared by the method.
[0039] Example 1
[0040] 1. Dissolve 8g APEG 350 and 6g 2-acrylamide-2-methylpropanesulfonic acid in 56g deionized water, adjust the pH to 7.0 with 5% mass concentration sodium hydroxide solution, add 2.8g Tween 40, and stir with a magnetic stirrer to fully dissolve it; continue to add 4.2g polyethylene glycol monomethyl ether acrylate, 2.8g dodecyl dimethyl allyl ammonium chloride, 5.6g styrene and 1.4g Span20; use a shear emulsifier to pre-emulsify for 30min at 2000r / min and then transfer to a reaction device; add 0.14g ammonium persulfate when the temperature is raised to 75°C in a nitrogen environment, use a stirrer, maintain the stirring speed at 400r / min, continue the reaction for 6 hours, and cool and take out to obtain a nano lubricating rubber brush.
[0041] 2. Mix 7g of nano rubber brush, 1g of zinc dialkyl dithiophosphate, 3g of 200 mesh elastic graphite and 80g of 3# white oil in a heatable high-speed stirring device, maintain a speed of 4000r / min at 60°C, and stir for 30min to fully dissolve, disperse and mix. After completion, a nanocomb polymer extreme pressure lubricant is obtained.
[0042] Example 2
[0043] 1. Dissolve 10g APEG400 and 8g N,N-dimethylacrylamide in 120g deionized water, adjust the pH to 7.0 with 5% mass concentration sodium hydroxide solution, add 1.8g Tween 60, and stir with a magnetic stirrer to fully dissolve it; continue to add 9g octadecyl acrylate, 3.6g hexadecyl dimethyl allyl ammonium chloride, 10.8g styrene and 5.4g Span40; use a shear emulsifier to pre-emulsify for 30min at 2000r / min and then transfer to a reaction device; add 0.18g ammonium persulfate when the temperature is raised to 80°C in a nitrogen environment, use a stirrer, maintain the stirring speed at 400r / min, continue the reaction for 6 hours, and then cool and take out to obtain a nano-lubricating rubber brush.
[0044] 2. Mix 10g of nano rubber brush, 3g of dialkyl dithiophosphate molybdenum oxide, 1.5g of 200 mesh elastic graphite, 1.5g of 2000 mesh boron nitride and 100g of 5# white oil in a heatable high-speed stirring device, maintain a speed of 4000r / min at 60°C, and stir for 30min to fully dissolve, disperse and mix. After completion, a nanocomb polymer extreme pressure lubricant is obtained.
[0045] Example 3
[0046] 1. Dissolve 6g APEG 500 and 4g N, N-diethylacrylamide in 40g deionized water, adjust the pH to 7.0 with 10% mass concentration sodium hydroxide solution, add 2g Tween 80, and stir with a magnetic stirrer to fully dissolve it; continue to add 5g polyethylene glycol monomethyl ether acrylate, 4g dodecyl dimethyl allyl ammonium chloride, 4g styrene and 3g Span20; use a shear emulsifier to pre-emulsify for 30min at 2000r / min and then transfer to a reaction device; add 0.2g ammonium persulfate when the temperature is raised to 85°C in a nitrogen environment, use a stirrer, maintain the stirring speed at 400r / min, continue the reaction for 6 hours, and then cool and take out to obtain a nano lubricating rubber brush.
[0047] 2. Mix 10g of nano rubber brush, 2g of dialkyl dithiophosphate oxygen molybdenum, 1g of dialkyl dithiophosphate zinc, 3g of 800 mesh talc and 80g of 10# white oil in a heatable high-speed stirring device, maintain a speed of 4000r / min at 60°C, and stir for 30min to fully dissolve, disperse and mix. After completion, a nanocomb polymer extreme pressure lubricant is obtained.
[0048] Comparative Example 1
[0049] The technical solution adopted is: removing the acrylate monomer on the basis of Example 1;
[0050] 1. Dissolve 8g APEG 350 and 6g 2-acrylamide-2-methylpropanesulfonic acid in 56g deionized water, adjust the pH to 7.0 with 5% mass concentration sodium hydroxide solution, add 2.8g Tween 40, and stir with a magnetic stirrer to fully dissolve it; continue to add 2.8g dodecyl dimethyl allyl ammonium chloride, 5.6g styrene and 1.4g Span20; use a shear emulsifier to pre-emulsify for 30min at 2000r / min and then transfer to a reaction device; add 0.14g ammonium persulfate when the temperature is raised to 75°C in a nitrogen environment, use a stirrer, maintain the stirring speed at 400r / min, continue the reaction for 6 hours, and then cool and take out to obtain a nano lubricating rubber brush.
[0051] 2. Mix 7g of nano rubber brush, 1g of zinc dialkyl dithiophosphate, 3g of 200 mesh elastic graphite and 80g of 3# white oil in a heatable high-speed stirring device, maintain a speed of 4000r / min at 60°C, and stir for 30min to fully dissolve, disperse and mix. After completion, a nanocomb polymer extreme pressure lubricant is obtained.
[0052] Comparative Example 2
[0053] The technical solution adopted is: removing the hydrophobic cationic monomer on the basis of Example 2;
[0054] 1. Dissolve 10g APEG400 and 8g N,N-dimethylacrylamide in 120g deionized water, adjust the pH to 7.0 with 5% mass concentration sodium hydroxide solution, add 1.8g Tween 60, and stir with a magnetic stirrer to fully dissolve it; continue to add 9g octadecyl acrylate, 10.8g styrene and 5.4g Span40; use a shear emulsifier to pre-emulsify for 30min at 2000r / min and then transfer to a reaction device; add 0.18g ammonium persulfate when the temperature is raised to 80°C in a nitrogen environment, use a stirrer, maintain the stirring speed at 400r / min, continue the reaction for 6 hours, and then cool and take out to obtain a nano-lubricating rubber brush.
[0055] 2. Mix 10g of nano rubber brush, 3g of dialkyl dithiophosphate molybdenum oxide, 1.5g of 200 mesh elastic graphite, 1.5g of 2000 mesh boron nitride and 100g of 5# white oil in a heatable high-speed stirring device, maintain a speed of 4000r / min at 60°C, and stir for 30min to fully dissolve, disperse and mix. After completion, a nanocomb polymer extreme pressure lubricant is obtained.
[0056] Comparative Example 3
[0057] The technical solution adopted is: removing the strongly adsorbed monomer on the basis of Example 3;
[0058] 1. Dissolve 6g APEG 500 in 40g deionized water, adjust the pH to 7.0 with 10% mass concentration sodium hydroxide solution, add 2g Tween 80, and stir with a magnetic stirrer to fully dissolve it; continue to add 5g polyethylene glycol monomethyl ether acrylate, 4g dodecyl dimethyl allyl ammonium chloride, 4g styrene and 3g Span20; use a shear emulsifier to pre-emulsify for 30min at 2000r / min and then transfer to a reaction device; add 0.2g ammonium persulfate when the temperature is raised to 85°C in a nitrogen environment, use a stirrer, maintain the stirring speed at 400r / min, continue the reaction for 6 hours, and then cool and take out to obtain a nano lubricating rubber brush.
[0059] 2. Mix 10g of nano rubber brush, 2g of dialkyl dithiophosphate oxygen molybdenum, 1g of dialkyl dithiophosphate zinc, 3g of 800 mesh talc and 80g of 10# white oil in a heatable high-speed stirring device, maintain a speed of 4000r / min at 60°C, and stir for 30min to fully dissolve, disperse and mix. After completion, a nanocomb polymer extreme pressure lubricant is obtained.
[0060] Comparative Example 4
[0061] The technical solution adopted is: removing the solid sacrificial agent on the basis of Example 3;
[0062] 1. Dissolve 6g APEG 500 and 4g N, N-diethylacrylamide in 40g deionized water, adjust the pH to 7.0 with 10% mass concentration sodium hydroxide solution, add 2g Tween 80, and stir with a magnetic stirrer to fully dissolve it; continue to add 5g polyethylene glycol monomethyl ether acrylate, 4g dodecyl dimethyl allyl ammonium chloride, 4g styrene and 3g Span20; use a shear emulsifier to pre-emulsify for 30min at 2000r / min and then transfer to a reaction device; add 0.2g ammonium persulfate when the temperature is raised to 85°C in a nitrogen environment, use a stirrer, maintain the stirring speed at 400r / min, continue the reaction for 6 hours, and then cool and take out to obtain a nano lubricating rubber brush.
[0063] 2. Mix 10g of nano rubber brush, 2g of dialkyl dithiophosphate oxymolybdenum, 1g of dialkyl dithiophosphate zinc and 80g of 10# white oil in a heatable high-speed stirring device, maintain a speed of 4000r / min at 60°C, and stir for 30min to fully dissolve, disperse and mix. After completion, a nanocomb polymer extreme pressure lubricant is obtained.
[0064] Performance evaluation method
[0065] 1. Evaluation of lubricant temperature resistance and durability
[0066] The conventional addition amount of the lubricant of the present invention is 1% to 3% by mass. 2% by mass of the lubricant is added to 400 mL of the base slurry, and the mixture is stirred at 4000 rpm for 20 minutes on a high-speed stirrer. The prepared sample is transferred to a high-temperature aging tank, and after aging at 200° C. for 24 hours, 48 hours, and 72 hours, the apparent viscosity, API filtration loss, foaming volume, and lubricity of the drilling fluid are measured.
[0067] The experimental results are shown in Table 1;
[0068] Table 1
[0069]
[0070]
[0071] It can be seen from Table 1 that with the increase of aging time, the apparent viscosity of the sample of the embodiment increases slightly due to the influence of high-temperature gelation of the base slurry, and the filtration loss also increases slightly. The foaming volume is very small, and after 72 hours of high-temperature aging, the reduction rate of the lubrication coefficient remains above 90%, indicating that the sample of the embodiment has good lubrication persistence. Comparative Example 1 removes the long-chain acrylates, and Comparative Example 2 removes the long-chain hydrophobic cationic monomers, which destroys the comb-type molecular structure of the lubricant, not only significantly increasing the filtration loss of Comparative Example 1 and Comparative Example 2, but also significantly reducing its lubricity. Comparative Example 3 removes the strong adsorption monomer. The basis for the comb-type lubricant to work is that it can be adsorbed on the surface of clay particles through adsorption groups, and the hydrophobic side chains stretch in the liquid phase to form a lubricating layer for lubrication. Therefore, the lubricity of Comparative Example 3 is poor, and the foaming degree after high-temperature aging is more serious, and the filtration loss is higher. Comparative Example 4 removes the solid sacrificial agent. It can be seen that the lubricity of the drilling fluid decreases rapidly after long-term aging. This is because the polymer lubricating rubber brush has weaker temperature resistance than the solid sacrificial agent, which is the essential property of the polymer that cannot be changed. When a solid sacrificial agent is contained, the solid particles are interspersed in the comb-shaped side chains of the comb-shaped polymer and play a certain protective role. When subjected to pressure and compression, the solid particles have a shear slip effect similar to that of graphite, playing a "force unloading" role, allowing the comb-shaped polymer to better play its lubricating role.
[0072] 2. Evaluation of lubricity of lubricants in high-density saturated salt systems
[0073] Preparation of high-density saturated brine drilling fluid: Under high-speed stirring at 8000rpm, add 8g of attapulgite, 12g of high-temperature and salt-resistant fluid loss reducer, 20g of ultrafine calcium carbonate, 12g (3%) of lubricant samples of the embodiments and comparative examples prepared by the present invention, 140g (35%) of sodium chloride to 400mL of base slurry, and adjust the system density to 2.0g / cm3 with barite. After adding each material, high-speed stirring is carried out for 20min. Attapulgite, high-temperature and salt-resistant fluid loss reducer, ultrafine calcium carbonate, and barite are provided by Shandong Deshunyuan New Materials Technology Co., Ltd.
[0074] The prepared drilling fluid sample was transferred into a high temperature aging tank, aged at 200°C for 16 hours, and then stirred at 8000 rpm for 20 minutes after cooling to measure the lubricity of the drilling fluid system. The experimental results are shown in Table 2.
[0075] (1) Evaluation of drilling fluid rheological filtration performance
[0076] Preparation of base slurry: Slowly add 20g bentonite and 0.8g sodium carbonate into 400mL distilled water while stirring. Stir for 20min at 10000rpm on a high-speed stirrer and then seal and cure at room temperature for 24h.
[0077] The apparent viscosity of the prepared drilling fluid and the API filtration loss of the drilling fluid are evaluated according to the standard "GB / T 16783.1-2014 Field Test of Drilling Fluids in the Petroleum and Natural Gas Industry Part 1 Water-based Drilling Fluids". The value of Φ600 (viscosity reading at 600rpm) is measured using a six-speed rotary viscometer, and the apparent viscosity of the drilling fluid is calculated according to the following formula:
[0078] Apparent viscosity (AV) = 0.5 × Φ600 (1)
[0079] (2) Drilling fluid foaming performance test
[0080] Measure 400 mL of base slurry, add the prepared lubricant to the drilling fluid base slurry, stir at 6000 rpm on a high-speed mixer for 20 min, then pour the high-speed stirred drilling fluid into a measuring cylinder and read the readings, and record the volume change of the drilling fluid before and after high-speed stirring.
[0081] Foaming volume = test drilling fluid volume - 400 (2)
[0082] (3) Determination of drilling fluid lubricity
[0083] According to Q / SY 17088-2016 Technical Specifications for Liquid Lubricants for Drilling Fluids, the EP-B extreme pressure lubrication tester is used to test the extreme pressure lubrication coefficient. The operation steps are as follows: First, calibrate the lubrication tester with distilled water, test the torque reading of distilled water, and ensure that the torque reading of distilled water is between 32-38. Replace the distilled water with the drilling fluid to be tested, and read the torque reading of the tested drilling fluid. Calibrate the machine with distilled water before each torque test. Calculate the lubrication coefficient reduction rate η according to the following formula.
[0084] Lubrication coefficient reduction rate
[0085] Where: η—lubrication coefficient reduction rate, %;
[0086] —Extreme pressure lubrication coefficient of base slurry;
[0087] —Extreme pressure lubrication coefficient of drilling fluid.
[0088] According to Q / SY 17088-2016 Technical Specifications for Liquid Lubricants for Drilling Fluids, the adhesion coefficient was determined using a JK-type unstuck fluid analyzer. The test conditions were a pressure difference of 3.5 MPa, a filtration time of 30 minutes, and the adhesion coefficients of 5 minutes, 10 minutes, 15 minutes, 30 minutes, and 45 minutes were read and calculated after the adhesion disk adhered to the mud cake. The adhesion coefficient reduction rate K was calculated according to the following formula.
[0089] Adhesion coefficient reduction rate
[0090] Where: K—adhesion coefficient reduction rate, %;
[0091] μ0—adhesion coefficient of base slurry at 45 minutes;
[0092] μ1—Adhesion coefficient of drilling fluid sample for 45 minutes.
[0093] The lubricity evaluation results under high density saturated salt conditions are shown in Table 2;
[0094] Table 2
[0095] sample Lubrication coefficient reduction rate (%) Adhesion coefficient reduction rate (%) Example 1 82.53 65.3 Example 2 83.26 64.8 Example 3 82.47 65.2 Comparative Example 1 72.69 52.9 Comparative Example 2 73.65 55.3 Comparative Example 3 75.71 56.4 Comparative Example 4 76.33 58.7
[0096] It can be seen from Table 2 that the samples of the examples still have good lubricity in the high-density saturated salt drilling fluid system, the lubricity coefficient reduction rate of the examples is more than 80%, and the adhesion coefficient reduction rate is more than 60%. Comparative Example 1 removes the long-chain acrylates, and Comparative Example 2 removes the long-chain hydrophobic cationic monomers, both of which destroy the comb-type molecular structure of the lubricant, causing its lubricity to be significantly reduced. Comparative Example 3 removes the strong adsorption monomer, which not only reduces the lubricity coefficient of the drilling fluid, but also affects the filtration loss, resulting in a slight increase in the filtration loss and thickening of the filter cake, thereby reducing the lubricity; Comparative Example 4 removes the solid sacrificial agent, but the comb-type polymer molecules can still play a role, so it still has a certain lubrication effect.
[0097] The above results indicate that the lubricant sample has good temperature and salt resistance and is suitable for use in high-density drilling fluids.
[0098] The nano-comb polymer extreme pressure lubricant mentioned in the present invention has good extreme pressure lubrication performance, good lubrication persistence, and still has good lubrication performance under high temperature, high pressure, high salt and high density conditions. The basis for its good lubrication performance is its special nano-comb structure and the synergistic coordination of various components; the nano-comb polymer lubricant is firmly adsorbed on the surface of clay particles under the strong adsorption group and cationic electrostatic action, which is the basis for the lubricant to work. Long-chain acrylates and long-chain hydrophobic cationic monomers constitute a comb-type structure. The comb-type structure polymer has good temperature and salt resistance. The hydrophobic side chain stretches in the high-salinity liquid phase and forms a lubricating layer with white oil for lubrication. The solid sacrificial agent has good temperature resistance and lubricity, and is interspersed in the comb-type side chain of the comb-type polymer. When the friction between the contact surfaces is stressed, the solid particles have a shear slip effect similar to that of graphite, which plays a "unloading" role. On the one hand, it plays a lubricating effect, and on the other hand, it protects the comb-type structure side chain and maintains its lubricating effect, thereby ensuring that the lubricant has good persistence. The extreme pressure anti-wear agent can form an extreme pressure chemical protective film on the surface of the metal drill bit, ensuring that the lubricant has good extreme pressure lubrication performance.
[0099] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A method for preparing a nanocomb polymer extreme pressure lubricant for drilling fluid, characterized in that: The following steps are involved: S1, dissolving allyl polyoxyethylene ether and a strong adsorption monomer in deionized water to prepare a mixed solution, adjusting the pH of the mixed solution to 7.0-8.0, adding emulsifier A and stirring evenly; S2, continue to add acrylate monomer, hydrophobic cationic monomer, styrene and emulsifier B in sequence and perform pre-emulsification; S3, adding an initiator after heating in a nitrogen environment, and cooling after the reaction is completed to obtain a nano-lubricating rubber brush; S4, mixing the nano-lubricating rubber brush, the extreme pressure anti-wear agent, the solid sacrificial agent and the white oil to obtain a nano-comb type polymer extreme pressure lubricant; The concentration of the mixed solution is 15% to 25%, and the mass ratio of allyl polyoxyethylene ether to the strong adsorption monomer is (3 to 5): (2 to 4); The mass ratio of the total mass of the emulsifier A, acrylate monomer, hydrophobic cationic monomer, styrene, emulsifier B, initiator, allyl polyoxyethylene ether and strongly adsorbing monomer is (1-2): (3-5): (2-4): (4-6): (1-3): (0.1-0.2): 10; The strong adsorption monomer is selected from one or more of acrylamide, N,N-dimethylacrylamide, N,N-diethylacrylamide, and 2-acrylamide-2-methylpropanesulfonic acid; The nano-lubricating rubber brush is uniformly mixed with an extreme pressure anti-wear agent, a solid sacrificial agent and white oil in a ratio of (7-10): (1-3): (3-5): (80-100); The solid sacrificial agent is one or more of boron nitride, elastic graphite and talcum powder.
2. The method for preparing a nanocomb polymer extreme pressure lubricant for drilling fluid according to claim 1, characterized in that: The allyl polyoxyethylene ether is selected from one or more of APEG 350, APEG 400 and APEG 500.
3. The method for preparing a nanocomb polymer extreme pressure lubricant for drilling fluid according to claim 1, characterized in that: The emulsifier A is a Tween series emulsifier, and the Tween series emulsifier is selected from one or more of Tween 40, Tween 60 and Tween 80; the emulsifier B is a Span series emulsifier, and the Span series emulsifier is selected from one or more of Span 20, Span 40 and Span 60.
4. The method for preparing a nanocomb polymer extreme pressure lubricant for drilling fluid according to claim 1, characterized in that: The acrylate monomer is selected from one or more of octadecyl acrylate, polyethylene glycol monomethyl ether acrylate, 2-dodecyl acrylate, and lauryl methacrylate.
5. The method for preparing a nanocomb polymer extreme pressure lubricant for drilling fluid according to claim 1, characterized in that: The hydrophobic cationic monomer is selected from one or more of dodecyldimethylallylammonium chloride, tetradecyldimethylallylammonium chloride, hexadecyldimethylallylammonium chloride, and carboxymethyloctadecylmethyldiallylammonium chloride.
6. A water-based drilling fluid, characterized in that: The invention comprises a nanocomb polymer extreme pressure lubricant prepared by the method according to claim 1.
Citation Information
Patent Citations
Comb-like polymer fluid loss additive for drilling fluid and preparation method thereof
CN101967369A
Polymer brush lubricant for water-based drilling fluid as well as preparation method and application of polymer brush lubricant
CN114805670A